If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(8 + -3k) + 3k = -224 (8 * -7 + -3k * -7) + 3k = -224 (-56 + 21k) + 3k = -224 Combine like terms: 21k + 3k = 24k -56 + 24k = -224 Solving -56 + 24k = -224 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '56' to each side of the equation. -56 + 56 + 24k = -224 + 56 Combine like terms: -56 + 56 = 0 0 + 24k = -224 + 56 24k = -224 + 56 Combine like terms: -224 + 56 = -168 24k = -168 Divide each side by '24'. k = -7 Simplifying k = -7
| 7/9-8/9 | | 4/9-2/5c=4 | | 500=22.7x+304 | | 22x-38=12x-98 | | 1100+800+4x=700+300+7x | | 4x-6x+25=3x+40 | | 21x-24=20x-26 | | 21x-26=23x-10 | | -4x=78 | | 80+0.70x=50+0.90x | | 4x+(5)=6 | | 2x/7-4=6x/7 | | 2.6y-3.4+6.1y=4.9 | | 5x-4(4)=-3 | | 30+100+y=x | | 5x(-20/11)-y=-10 | | 100-r=19/7 | | 3.2x=15 | | -x-20=31 | | 5x-12=188 | | C=5/9•(394-32)= | | X=10-cos^2x/-4cosx | | C=5/9•(394-32) | | 6x-3x+6=-4x+7 | | 15+.50y=22 | | 1/6x=-4/6 | | 104h=13 | | 5[4-(8x-4)]+4x=0 | | (x-3)(x+3)+11=6x | | 8f-3(f+8)=66 | | 2(-7k+4)=-13 | | 2t^2-16r=0 |